Pengabdian Masyarakat “We Buy We Distribute” sebagai Upaya Membantu Petani di Ngablak, Magelang Survive - Arisanto, Puguh Toko; Rizky, Lucitania; Wibawa, Adi; Pratiwi, Tiffany Setyo; Iswardhana, Muhammad Ridha; Chotimah, Hidayat Chusnul (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The agricultural sector is one of the main pillars in the national economy because it makes a significant contribution to the Gross Domestic Product (GDP), absorbs labor, and is the main livelihood for most Indonesians, especially in rural areas. Among various agricultural subsectors, vegetables have an important role as a commodity that not only meets the needs of household consumption, but also becomes a major source of income for farmers. However, vegetable farmers are often faced with serious problems that directly impact their well-being. One of the main problems is price instability. During the harvest, the abundance of production causes the price of vegetables to fall drastically so that it is not able to cover the capital costs that have been incurred. This is experienced by vegetable farmers in Ngablak District, Magelang Regency, where the selling price of vegetables at harvest time is very cheap, often even below production costs, so that farmers suffer big losses. Reflecting on these problems, this community service activity is present with the theme "we buy, we distribute." This concept is carried out by buying vegetables directly from local farmers at a more decent price than the market price during the harvest. The vegetables that have been purchased are then not resold for profit, but are distributed for free to people who really need them, especially residents in Kepanjen Hamlet, Trimulyo, Sleman. Thus, this activity provides dual benefits, namely helping farmers to continue to earn a decent income and supporting community food security through the distribution of vegetables for free. This program is also a form of social solidarity between farmers and the community, as well as a simple but real solution in dealing with the problem of fluctuations in the price of agricultural products.